Models for Access to Maternal Smoking Cessation Support: a quasi-experiment to increase the engagement of pregnant women who smoke in National Health Service stop smoking services. (November 2016) - Bennett, L; Jones, A; Paranjothy, S
Abstract: Background: Maternal smoking is a key cause of poor health outcomes. In Wales, a third of pregnant women smoke before or during pregnancy, the highest prevalence of maternal smoking in the UK. Supporting women to stop smoking during pregnancy is a challenging area of public health. Models for Access to Maternal Smoking Cessation Support (MAMSS) aimed to examine the effectiveness of smoking cessation in pregnancy services delivered by specially trained practitioners. Methods: A non-randomised, quasi-experiment was undertaken across four Health Boards in Wales to assess the effectiveness of new models of service designed to increase the engagement of pregnant women in National Health Service (NHS) stop smoking services. Qualitative approaches were adopted to capture important contextual information and consider multiple perspectives. A flexible, bespoke intervention was offered to pregnant women in intervention sites (delivered by a specialist maternity support worker, a specialist midwife, or a specialist Stop Smoking Wales pregnancy adviser) and compared with usual care delivered by the national stop smoking service. Routine data were collected from maternity records and the NHS Stop Smoking Wales service. The primary outcome was the proportion of smokers who engaged with the service. Power calculations showed that 1168 pregnant smokers were required to detect a 15% difference in the proportion of pregnant smokers engaged with smoking cessation services (5% type I error rate and 90% power). Findings: 2756 women were identified by midwifery staff as pregnant smokers (978 in intervention and 1778 in control sites). The proportion of smokers who engaged with the service was significantly higher across intervention sites than control sites. The highest proportion was observed in Health Board area 3, which employed a maternity support worker to support women to quit smoking, where 64 of 181 pregnant smokers (35%, 95% CI 29–43) set a quit date and attended at least one treatment session compared with just two of 227 in usual care (1%, 0–3). This model cost about £500 per engaged smoker. Qualitative findings highlighted the acceptability and feasibility of delivering the service models. Interpretation: The maternity support worker model is effective in engaging pregnant women with stop smoking services and has the potential to improve future health outcomes. Funding: The research received funding and support in kind from Public Health Wales NHS Trust and the Health Boards involved. Cwm Taf University Health Board's Research and Development department funded their element of the study.